2017
DOI: 10.1186/s12943-017-0677-9
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Linc00152 promotes malignant progression of glioma stem cells by regulating miR-103a-3p/FEZF1/CDC25A pathway

Abstract: BackgroundGlioma is one of the most frequent intracranial malignant tumors. LncRNAs have been identified as new modulators in the origination and progression of glioma.MethodsQuantitative real-time PCR were conducted to evaluate the expression of linc00152 and miRNA-103a-3p in glioma tissues and cells. Western blot were used to determine the expression of FEZF1 and CDC25A in glioma tissues and cells. Stable knockdown of linc00152 or over-expression of miR-103a-3p in glioma stem cells (GSCs) were established to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
109
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(120 citation statements)
references
References 63 publications
11
109
0
Order By: Relevance
“…We subsequently confirmed that LINC00152 knockdown significantly suppresses glioma cell proliferation, migration, invasion, and tumor growth. Our results on the oncogenic role of LINC00152 are similar to the findings in a recently published paper by Yu and colleagues, where LINC00152 facilitated cell proliferation, migration, and invasion, while suppressing apoptosis in glioma stem cells by regulating the miR-103a-3p–FEZF1–CDC25A pathway [22]. …”
Section: Discussionsupporting
confidence: 90%
“…We subsequently confirmed that LINC00152 knockdown significantly suppresses glioma cell proliferation, migration, invasion, and tumor growth. Our results on the oncogenic role of LINC00152 are similar to the findings in a recently published paper by Yu and colleagues, where LINC00152 facilitated cell proliferation, migration, and invasion, while suppressing apoptosis in glioma stem cells by regulating the miR-103a-3p–FEZF1–CDC25A pathway [22]. …”
Section: Discussionsupporting
confidence: 90%
“…[29] Recent studies have shown that LINC00152 is highly expressed in a variety of tumors, such as, glioma, [30] nonsmall cell lung cancer, [31] gastric cancer, [32] etc. [29] Recent studies have shown that LINC00152 is highly expressed in a variety of tumors, such as, glioma, [30] nonsmall cell lung cancer, [31] gastric cancer, [32] etc.…”
Section: Discussionmentioning
confidence: 99%
“…Glioma cells were cultured in Dulbecco's modified Eagle medium (DMEM)/high glucose with 10% fetal bovine serum (FBS, Gibco, Carlsbad, CA, USA) and were maintained in a humidified incubator at 37°C with 5% CO 2 . GSCs were separated as described previously from tissue cells . Primary cells were detached with trypsin, washed once in FACs buffer (PBS containing 1%‐2% BSA and 5 mM EDTA), then stained with anti‐CD24‐FITC (Invitrogen, Carlsbad, CA, USA) and anti‐CD133‐PE (Invitrogen) using 10 μl of antibody per 10 6 cells, and incubated at 4°C for 15 minutes.…”
Section: Methodsmentioning
confidence: 99%